DISTORSI BENTUK IMAJINER UNTUK PENCAPAIAN HARMONI - Yudha, I Made Bendi (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
Art is an expression of feeling and soul. It is the crystallization of an idea that derives from imaginative soul experience through observation, deep thinking on the phenomena of social environment. Then, through intellectual ability and internal or external motivation raises an intuitive vibration that stimulates inner emotion to be artistically expressed through the language of visual art work. For Balinese, rerajahan is one of literature works which has a value and symbolic meaning of the all life aspects both on macro and micro cosmos. It is also depicting the energy that is a symbol of gods and evil character. These all are the reflection of dualistic. These concepts which are overlapping and interdependent to each other must be kept appropriately in order to maintain the harmony. The concept of harmony that exists in rerajahan seems neglected or even left behind when we compare with the phenomena life in society. This can be seen on the inappropriate acts either to the nature or human life. As we know, an exploitation of natural resources, the inappropriate authority acts of particular parties or people, gender, discrimination on law and human rights, and inappropriate acts of state administration. These phenomena generally make the increase of ecological crisis and the degradation of human moral or get the level of social poverty even worse. At present, these inappropriate acts are getting out of control because the spread takes place both on the low and elite levels. So, these are very complex phenomena just like a messy thread that needs to be solved holistically. The comprehension of all the above values have brought some ideas regarding on the life meanings in which its philosophical concepts in an abstract way astatically are implemented into the painting art work by combining both the representative and abstractive concepts. It is also implemented in term of applying varied line, color, and textures. It is hope that impasto technique can represent certain symbol and meaning in order to give the value of the authenticity of the art work which has an artistic personal values and novelty. Key word : Painting art work, distortion of imaginary shape and harmony